Experimental research on high-speed dry milling performance of large-area nodular cast iron. Issue 1 (February 2020) - Yan, P; Wang, Y B; Chen, K J; Ma, B X; Xiao, Y L; Wang, X B
Abstract: Nodular cast iron was with excellent casting performance, abrasion resistance, strength, and toughness, and successfully applied in large components with high requirements of complex load, strength, etc. While high-efficiency precision machining of large-size plane nodular cast iron was difficult in actual production. In this study, the influence of cutting parameters on cutting performance in the precision milling of large size nodular cast iron was systematically investigated. The spindle peak-power ratio increased linearly as the increase of cutting speed and cutting depth, while it was the lowest at a feed rate of 0.10 mm on account of the minimum cutting depth effect. The surface roughness Ra was decreased linearly as the increase of cutting speed, while the change trend of Ra was not significant as feed rate and cutting depth. As the cutting speed increased, the flaky chips shortened and the helical chip crimped intensity; as the increase of feed rate or longitudinal cutting depth, the length of the foil or ribbon chips increased and the crimp of the helical chip increased. The results could be the guide of the actual machining process of nodular cast iron engine box and cover to improve the machining efficiency and surface quality.